In the consumer society the concept of cultural space scaling: The Case of Istanbul - ERÇETİN, ARZU (Istanbul Kultur Univ, Atakoy Campus, Bakırkoy, Istanbul, 34156, Turkey, 2018)
The scaling of the concept of space by the aspect of culture in consumption societies; example of Istanbul. When the concept of space is considered as an object in consumotion societies, we could examine and reveal this concept in both making definition from past to present, and guiding life by cultural and dialectical sense. Also by looking within the scope of definitions which describe quality, aesthetically and ergonomically. From the cultural point of view, the concept of space can be defined as afar from simplicity and functionality according to its field of application, and especially in contemporary Turkey, it is faced with cruel and ironic comments in the aspect of critics. But these ironic comments made by the denomination who have no academic andtheoretical back grounds, are completely softened against the construction which does not have cultural features and they are shaped to support the structures that change the city identity of Istanbul. The purpose of this notification is to evaluate the space scales presented by the constructor companies to Istanbul where continuosly getting immigrants and everyday with a new concrete formation, leave its historical culture to vertical rising up linear silhouettes, with cooperation of TOKI according to their selected sample projects.
Keywords: Cultural Self; City Identity; Urban Design; Space; Consumption; Scale